Implementasi Manajemen Berasis Sekolah di UPTD SPNF SKB Kota Salatiga - Siah, Ina; Miyono, Noor (PGRI Kota Semarang, 2024)
The new education paradigm in the National Education System Law Number 20 of 2003 is the embodiment of one of the reform demands for changing the government system from centralization to decentralization. The concept of decentralization in education means the delegation of authority from the central government to regional governments to make management decisions and prepare their own plans to overcome educational problems by referring to the national education system. Providing autonomy for the implementation of education in schools in order to improve the quality of education requires a more conducive management approach so that it can accommodate all desires while empowering various components of society effectively. It is within this framework that School Based Management (SBM) becomes one of the educational management policies offered in the new paradigm. The aim of this research is to determine the principles and implementation of school-based management (MBS) functions in UPTD SPNF SKB Salatiga City. Data collection techniques are carried out through observation, interviews and documentation. The informants in this research were the school principal, curriculum development team, inventory officer, and treasurer. The data analysis technique using descriptive analysis includes three main things, namely data reduction, data presentation, and drawing conclusions or verification. Test the validity of the data using triangulation. The results of this research can be concluded that (1) UPTD SPNF SKB Salatiga City has implemented school-based management principles in the implementation of non-formal education. (2) UPTD SPNF SKB Salatiga City implements school-based management functions in curriculum management, student management, educator and education staff management, facilities and infrastructure management, financing management, school and community relations management, and cultural and environmental management.